PERIPHERAL VENOPUNCTION AND ITS MAINTENANCE: SOCIAL REPRESENTATION BY WOMEN IN CESAREAN SECTION - Morais, Thainá Ribeiro Rezende de; Krempser, Paula; Arreguy-Sena, Cristina; Dutra, Herica Silva; Leonel, Mariléia; Silva, Flávia Reis da; Lacerda, Isabela Verônica da Costa (Cogitare Enfermagem, 2023)
Objective: to identify and analyze the social representations and their dimensions about peripheral venous catheterization and its maintenance for anesthetic-surgical purposes in women undergoing cesarean section. Method: qualitative study of exploratory-descriptive type grounded by the Theory of Social Representations with the participation of 120 women and carried out in a public hospital in the state of Minas Gerais - Brazil, between 2019 and 2020. Evocations collected by interviews with application of the technique of free association of non-hierarchical words with prototypical analysis and by similarity in the EVOC and IRAMUTEQ software. Results: the present social representation addresses feelings in the behavioral dimension of stress, which are related to insecurity and fear of the pain of the needle, the surgical procedure, and the restriction of movements. Conclusion: the research contributes to a reflection on the need to resize nursing care before the difficulties faced by women in the triple experience of stress: cesarean section; venous catheterization; and the difficulty of performing postpartum care.